Determinants of contraceptive use prior to onset of childbearing among ever-married women in Indonesia: a secondary data analysis - Sarah Muharomah; Linnea A. Zimmerman (BMC Women's Health)
Abstract Background Despite high rates of early marriage and adolescent childbearing in Indonesia—which increase risks for both maternal and child health—family planning efforts largely focus on birth spacing or limiting the number of children. Few programs specifically address the reproductive needs of ever-married women who wish to prevent or delay their first birth. This study investigates the sociodemographic factors influencing contraceptive use prior to childbearing among ever-married women in Indonesia. Methods We analyzed weighted data from 121,916 ever-married women using the 2002–2017 Indonesia Demographic and Health Surveys. Variables were selected based on prior research and bivariate screening. Univariate and multiple survey logistic regression analyses were performed; model selection was guided by the Akaike Information Criterion, and Nagelkerke R-square quantified the explained variance. Results Overall, 4.66% of ever-married women reported using contraception before having any children. Younger women (15–19 years), those preferring a smaller family size, being employed, and residing in Java were significantly associated with higher usage. Contrary to conventional assumptions, the poorest wealth quintile had notably high odds of pre-childbearing contraceptive use, second only to the richest. Interactions involving education and rural residence highlighted the multifaceted nature of these reproductive decisions. Discussion These findings underscore the need for targeted policies to address diverse socioeconomic barriers and to empower women who wish to delay their first birth.